Treatment of Rat Lymphedema by Propeller Lymphatic Tissue Flap Combined with Nanofibrillar Collagen Scaffolds - Dionyssiou, Dimitrios; Nguyen, Dung; Topalis, Anastasios; Deptula, Peter; Paukshto, Michael; Zaitseva, Tatiana; Demiri, Efterpi; Cheva, Angeliki; Rockson, Stanley (Journal of Reconstructive Microsurgery, 2023)
Background The aim of our study was to evaluate a new propeller vascularized lymphatic tissue flap (pVLNT) combined with aligned nanofibrillar collagen scaffolds (CS) (BioBridge) in reducing lymphedema in the rat lymphedema model.Methods Unilateral left hindlimb lymphedema was created in 15 female Sprague–Dawley rats following inguinal and popliteal lymph nodes (LN) resection and radiation. An inguinal pVLNT was elevated from the contralateral groin and transferred through a skin tunnel to the affected groin. Four collagen threads were attached to the flap and inserted in the hindlimb at the subcutaneous level in a fan shape. The three study groups consisted of group A (control), group B (pVLNT), and group C (pVLNT + CS). Volumetric analysis of both hindlimbs was performed using micro-computed tomography imaging before the surgery (at initial time point) and then at 1 and 4 months, postoperatively, and the relative volume difference (excess volume) was measured for each animal. Lymphatic drainage was assessed by indocyanine green (ICG) fluoroscopy for number and morphology of new collectors and the time required for ICG to move from injection point to the midline.Results Four months after the induction of lymphedema, an increased relative volume difference remained in group A (5.32 ± 4.74%), while there was a significant relative volume reduction in group B (−13.39 ± 8.55%) and an even greater reduction in group C (−14.56 ± 5.04%). ICG fluoroscopy proved the functional restoration of lymphatic vessels and viability of pVLNT in both B and C groups. Notably, only group C demonstrated statistically significant improvements in lymphatic pattern/morphology and in the number of lymphatic collectors as compared with the control group A.Conclusion The pedicle lymphatic tissue flap combined with SC is an effective procedure for the treatment of lymphedema in rats. It can be easily translated into treatment of humans' lower and upper limb lymphedema and further clinical studies are warranted.
Keywords: lymphedema; vascularized lymph node transfer; collagen scaffolds; guided lymphangiogenesis